A dual wide-band ingestible antenna design for wireless capsule endoscopy - Dubey R.; Singh A.; Srivastava S.K.; Ajitesh; Meshram M.K. (My University, 2025)
In this paper, we present a dual wide-band ingestible antenna design for wireless capsule endoscopy (WCE) biotelemetry applications. The design process employs Characteristic Mode Analysis (CMA) and driven modal analysis. The effectiveness of the prototype antenna is afterward assessed through measurements using a tissue-equivalent phantom liquid model. We investigate the effects of antenna implantation depth and capsule shell thickness on its performance, providing insights into practical considerations. The proposed dual-band antenna demonstrates good performance in both the 1.4 GHz Wireless Medical Telemetry Services (WMTS) and 2.45 GHz Industrial, Scientific, and Medical (ISM) bands, exhibiting measured impedance bandwidths of 36% and 22%, respectively. The measured peak realized gains are −22.9 dBi and −25.3 dBi for the WMTS and ISM bands, respectively, with a compact footprint of 78.5 mm2. To ensure health and safety and optimal performance, we evaluate the antenna's specific absorption rate (SAR) and link margin (LM). Additionally, we assess the performance of the proposed antenna in comparison with the state-of-the-art design for capsule antennas in WCE applications. © 2023 Elsevier GmbH